Degradable Gelatin-Based IPN Cryogel Hemostat for Rapidly Stopping Deep Noncompressible Hemorrhage and Simultaneously Improving Wound Healing - Huang, Ying; Zhao, Xin; Zhang, Zhiyi; Liang, Yongping; Yin, Zhanhai; Chen, Baojun; Bai, Lang; Han, Yong; Guo, Baolin (Chemistry of materials, 2020)
Biodegradable cryogel wound dressing which can stop deep noncompressible hemorrhage and simultaneously promote wound healing is a highly promising biomaterial in clinics. Here, we prepared a series of biodegradable interpenetrating polymer network (IPN) dry cryogel hemostats by cryo-polymerization of gelatin and dopamine. The IPN structure of cross-linked gelatin and polydopamine endows the cryogels good injectability, robust mechanical property, and shape memory property. The cryogels showed better whole blood-clotting capacity and more blood cell and platelet adhesion and activation than gauze and gelatin hemostatic sponge. The cryogels present less blood loss and shorter hemostasis time than gauze and gelatin hemostatic sponges in the mouse liver trauma model, rat liver incision model, and rabbit liver cross incision model. Especially, the hemostatic effect of the cryogel on deep narrow noncompressible hemorrhage was determined by the rabbit liver defect deep narrow noncompressible hemorrhage model. The cryogel rapidly stopped deep massive noncompressible hemorrhage in the swine subclavian artery and vein complete transection model. Besides, the component of polydopamine endows cryogels with excellent antioxidant activity and NIR irradiation-assisted photothermal antibacterial ability. Gelatin/dopamine cryogels were more effective in promoting wound healing than Tegaderm films. The developed biodegradable cryogels with a simple preparation process and low cost and which can be easily carried and used present huge potential as novel wound dressing for rapid hemostasis and promoting wound healing.